STUDI NILAI KALOR BRIKET CANGKANG KELAPA SAWIT SEBAGAI BAHAN BAKAR PADAT - Hudri Fauzun; Hendri Nurdin; Remon Lapisa; Sri Riski Putri Primandari (Jurnal Vokasi Mekanika (VoMek), 2024)
The fuel oil energy source used is currently experiencing a fuel supply shortage, so it is necessary to have alternative energy sources with renewable and environmentally friendly raw materials to anticipate the increasingly depleting oil fuel sources. One of them is utilizing biomass energy with agricultural waste as raw material which is processed into briquettes. The material used in this research is palm oil shells using tapioca adhesive which will be processed into briquettes as an alternative fuel. Through the process of making briquette products with variations in the composition of the mixture provided, quality calorific value can be achieved. The research results showed that the highest calorific value of palm oil shell briquettes was found in the 80% : 20% mixture variation, namely 13428.5904 Kj/Kg, and the lowest calorific value was found in the 60% : 40% mixture variation, namely 9139.76928 Kj/Kg .